Co-Signaling Molecules in Maternal–Fetal Immunity. Issue 1 (January 2017) - Xu, Yuan-Yuan; Wang, Song-Cun; Li, Da-Jin; Du, Mei-Rong
Abstract : Physiologically, a successful pregnancy requires the maternal immune system to recognize and tolerate the semiallogeneic fetus, and allow for normal invasion of trophoblasts. Thus, pregnancy complications are considered to be associated with dysfunctional maternal–fetal crosstalk. Co-signaling molecules are a group of cell surface molecules that positively or negatively modulate the immune response. Well studied in the fields of oncology and transplantation, they are also suggested to be involved in maternal–fetal crosstalk. Here, we review the latest knowledge on the expression and function of such co-signaling molecules, highlighting their immunoregulatory roles in maternal–fetal tolerance and decidual vascular remodeling, and their involvement in pathological pregnancies. This review may instruct future basic research on, and clinical applications for, maternal–fetal immunity. Trends: Co-signaling molecules, such as those involved in regulatory immune checkpoints [including programmed cell death 1 (PD-1) and cytotoxic T lymphocyte-associated protein 4 (CTLA-4), as well as others], have important modulatory effects on tumors, as well as in transplantation, infections, and autoimmune diseases. Thus, they have recently been highlighted as potential diagnostic and therapeutic targets for various pathologies. During normal pregnancy, the fetus is considered as a semiallogeneic transplant. Meanwhile, the immune defense against pathogens must remain uncompromised. Therefore, maternal–fetal tolerance is a special immunological phenomenon. Recently, co-signaling molecules have been found to be spatiotemporally expressed in thegravid uterus and to be involved in pregnancy maintenance by regulating maternal–fetal immunity and assisting decidual vascular remodeling. It is hypothesized that dysregulation of these molecules could lead to pregnancy loss and pregnancy complications. The incidence of pregnancy-related diseases is still high without efficacious strategies for diagnosis and treatment; thus, further evaluation and intervention of co-signaling molecules may be helpful in this respect.